Comparative study of fibrin glue, suturing and sutureless / glue-free limbal conjunctival autograft for primary pterygium surgery in patients attending a tertiary care hospital in Eastern India (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To compare the effectiveness, safety, and cost-effectiveness of three conjunctival autograft-fixing methods: fibrin glue, sutures, and no glue or sutures; to examine patient comfort, complications, recurrence, and postoperative outcomes; to determine whether fibrin glue or the sutureless/glue-free method is significantly better than traditional suturing in surgical efficiency, postoperative recovery, and long-term patient satisfaction. Methods: A prospective comparative study was conducted on 150 patients undergoing primary pterygium excision. Participants were randomly assigned to three groups: Group I (Fibrin Glue, n = 50), Group II (Suturing, n = 50), and Group III (Sutureless/Glue-Free, n = 50). Surgical duration, postoperative complications, recurrence rates, and patient-reported comfort were assessed at one week, six weeks, and six months. Statistical analysis was performed to evaluate differences between groups.Results: Surgical time was significantly shorter in the fibrin glue (24.05 ± 0.94 min) and sutureless (23.27 ± 0.87 min) groups compared with suturing (46.2 ± 1.34 min) (p < 0.001). Patients in the fibrin glue and sutureless groups reported greater postoperative comfort, while suturing was associated with increased pain, foreign body sensation, and tearing. Recurrence was slightly higher in the sutureless group (4 cases) compared with fibrin glue (2 cases) and suturing (2 cases), although the differences were not statistically significant.Conclusion: Compared with sutures, both fibrin glue and sutureless/glue-free fixation techniques reduce operative time and improve postoperative comfort. Sutureless fixation offers a cost-effective alternative suitable for low-resource settings, although fibrin glue provides superior stability and patient experience. Long-term studies are warranted to further evaluate recurrence risk and cost-effectiveness.
Keywords: Conjunctival Autograft; Tissue Adhesives; Surgical Sutures; Ophthalmologic Surgical Procedures; Pterygium